Implementasi Monitoring dan Evaluasi pada Pengembangan Koleksi Perpustakaan SMA Pasundan 8 Bandung - Arya, Ghaitsa Zahira; Hadiapurwa, Angga; Wulandari, Yayu; Nugraha, Hafsah (UNILIB : Jurnal Perpustakaan, 2024)
The school library plays a role in fulfilling information needs and improving the quality of teachers and students to achieve school goals. One of the high schools in Bandung City that has to carry out this role is Pasundan 8 High School. The school library concerned still needs to meet the standards, one of which is the standard collection aspect. Collection development can be done so that the collections owned by the library are diverse. The method used in this research is a descriptive quantitative method with data collection through observation, interviews, questionnaires, and documentation. Data were obtained from one source: library staff, three teachers, and seven students. The results show that the types of collections that can be developed are collections of fiction, non-fiction, and references. The library manager can do collection floating by submitting a request to the school or cooperating with other information institutions. In addition, library managers can also participate in various trainings so that they can develop collections in a digital direction. This is done so that groups in the library are more diverse and of higher quality for the entire school community.